Characterisation of amylase from Aspergillus flavus NSH9 obtained by solid-state fermentation of rice husks - Rosmawati, Saat (Universiti Malaysia Sarawak (UNIMAS), 2019)
A variety of agro-waste has been applied as the SSF substrate for the production of amylase by A. flavus and most of the research studies were conducted outside Malaysia. A few studies have applied rice husks as the SSF substrate, however, media supplements or additional nutrients were added. In this study, rice husk without any supplements was applied. Based on the amylolytic activity observed, rice husk alone was proven to be feasible as the SSF substrate for A flavus NSH9. Identity of the fungal isolate used was further verified by performing morphological analyses and SEM analysis on the conidial structure as to distinguish A. flavus from A. paraticus as both of them are closely resembled even at the genetically level. Process parameters such as initial moisture content of the substrate, incubation period and incubation temperature are the critical factors influencing the success of fermentation process. Different microbial strains/isolate with different fermentation substrates may have different process requirement. Thus, the fore mentioned parameters were studied and the optimal SSF condition for A. flavus NSH9 grown on rice husks in producing amylase was successfully determined (70 % of initial moisture content, 144 hours or 6 days and 30 oC). Subsequently, the extracted enzyme was partially purified by filtration through cellulose acetate filter and concentrated using Vivaspin 20. Starch hydrolysis analyses were performed on the enzymes as well as the fungus and results obtained (halo zones were observed) indicated the presence of amylolytic activities. Biochemical characterisation on the partially purified enzyme revealed that the highest amylolytic activity was achieved at 40 oC, 30 mins of incubation, starch concentration of 2% and pH 5.5 as well as pH 7. Monovalent and divalent metal ions studied were shown to influence the enzyme activities either by stimulatory or inhibitory. All the surfactants, denaturing agent and chelator studied were found to affect the enzyme either by increasing or reducing its activities. Based on these observations, the enzyme is suggested to be metallo-amylase which requires metal ion(s) as co-factor(s) in its active site for activity. Molecular investigation through native-PAGE, zymography and SDS-PAGE analyses have verified the activity of amylase with indication of at least two forms of amylases present in the extract. Further molecular analyses of protein sequencing applying MALDI-ToF have shown that the enzymes present were α-amylase and glucoamylase. Furthermore, only minimal major aflatoxin compounds (0.0017 ppm for the total of aflatoxin B2 and G2) was detected in the crude/partially purified enzymes of earlier culture and none in crude/partially purified enzymes of later fungal culture. The findings of this study would provide a platform in realising the development of local amylases for local industrial demands by utilising the local under-utilised agro-industrial wastes such as rice husks.